Abundance and Composition of Targeted Reef Fish in an Unprotected Coral Reef Ecosystem: A Case Study of Oransbari Bay - Duaitd Kolibongso; Toni Sitinjak; Roni Bawole (Universitas Diponegoro, 2025)
Reef fisheries particularly those targeting specific fish species are integral to the coral reef ecosystem. Unprotected sites typically exhibit substantial declines in fish densities due to fishing pressure. We conducted an analysis to determine whether the abundance of target fish species correlates with benthic community structure and changes in composition resulting from fishing activities. The point intercept transect (PIT) method was employed to evaluate coral reef condition, while underwater visual census (UVC) was utilized to assess target fish species at three sites in Oransbari Bay. The mean live coral cover in Oransbari Bay was measured at 20.2% ± 2.37 (mean ± standard error). Benthic cover exhibited variation, with rubble comprising 27.6% ± 3.73%, sand 29.3% ± 2.58%, dead coral 9.44% ± 2.91%, and turf algae 4.33% ± 3.47%. The target species group displayed diversity, with 13 species identified across six families: Acanthuridae, Lutjanidae, Serranidae, Caesionidae, Balistidae, and Mullidae. Reef fish abundance ranged from 3,146.7 to 9,986.7 individuals per hectare, with the Acanthuridae family demonstrating the highest abundance and diversity, as it was present at all locations. This study elucidates that the abundance and diversity of target reef fish species in unprotected areas are significantly influenced by coral cover and fishing activities. These findings provide crucial insights into the status of fish resources beyond protected areas in the Bird’s Head Peninsula, contributing valuable information for future management of coral reef ecosystems.